Sifting the ashes : retaining the hard-won lessons of Britain's Afghan War - Watling, Jack (Routledge, 2024)
The British military spent 20 years fighting in Afghanistan. Considering the UK's achievements against its objectives, defeat seems the most accurate description of the campaign's outcome. How institutions respond to and learn from failure is a good measure of their effectiveness. But Britain's war in Afganistan also saw considerable tactical and operational learning to solve complex problems. Not only are some of the solutions valuable, but the processes by which they were derived bear study. The question is whether these lessons will be retained. This Whitehall Paper delves into some of the many valuable and hard-won lessons that can be derived from a study of British operations in Afganistan, beginning a conversation as to their relevance for future British miliatry undertakings.
Keywords: Afghan War, 2001-2021 -- Participation, British.; Afghan War, 2001-2021 -- Campaigns -- Afghanistan.; elektronické knihy; electronic books